Treatment of cadmium-contaminated soil using ladle slag with and without CO₂ - Xu, Bo (2023)
Cement and lime are widely used to stabilize/solidify (S/S) contaminated soils, however, the production of ordinary Portland cement (OPC) and lime causes CO2 emission and consumption of energy and non-renewable resource. In this context, this study proposes a sustainable S/S approach by utilizing an industrial by-product, ladle slag (LS), and carbon dioxide (CO2), to substitute cement and lime for treating cadmium (Cd)-contaminated soil. In laboratory investigation, contaminated soils spiked by Cd with concentrations of 0–32,000 mg/kg were treated by LS with a binder content of 10 % and subjected to conventional curing and carbonation curing for different periods varying from 3 hours to 112 days. The results showed that LS with conventional curing could reduce the leaching of Cd, however, it was still less effective than OPC in S/S of Cd-contaminated soils under the same curing period of 28 days. When CO2 was introduced, LS with CO2 rapidly decreased the leaching of Cd in soils by five orders of magnitude, using only 104 hours to achieve better S/S efficacy than OPC with conventional curing for 28 days. The LS with carbonation curing also sequestered CO2 up to 16 % of LS mass and yielded higher strength than that without CO2.